Language Structure, Variation and Change The Case of Old Spanish Syntax - Mackenzie, Ian E. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book offers an original account of the dynamics of syntactic change and the evolving structure of Old Spanish that combines rigorous manuscript-based investigation, quantitative analysis and a syntactic approach grounded in Minimalist thinking. Its analysis of both successful and failed changes demonstrates the degree of unpredictability caused by the interaction of competing factors and will shed fresh light on the assumed unidirectionality of linguistic change. Importantly, it reveals that Old Spanish and modern Spanish are more similar to one another than is usually supposed and demonstrates that many of the differences between the two varieties are quantitative rather than qualitative. This theoretically sophisticated examination of historical corpora will provide an invaluable resource for students and scholars of Old and modern Spanish, historical linguistics, sociolinguistics and syntax. Ian E. Mackenzie is Professor of Spanish Linguistics at Newcastle University, UK. He is the author of seven books, as well as numerous articles in the fields of syntax, semantics and diachronic linguistics.